Analyzing The Impact of Price, Brand Perception, and Flavor Importance on Consumer Switching Behavior: A Case Study of Gudang Garam in The Indonesian Cigarette Market - Erlangga Nata Wijaya; Nila Armelia Windasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Indonesian cigarette industry is a highly competitive and heavily regulated market, where consumer preferences are influenced by various factors, including price, brand perception, and flavor. This study examines the key determinants of consumer switching behavior in the cigarette market, focusing on PT. Gudang Garam, a major tobacco producer in Indonesia. Over the past three years, the company has experienced a decline in market share, raising concerns regarding the effectiveness of its branding, pricing, and product offerings. This research aims to analyze the extent to which price, brand perception, and flavor importance affect consumer switching behavior. A quantitative approach was employed, using survey data collected through structured questionnaires. The data were analyzed using structural equation modeling to test the relationships among these variables. The findings indicate that price exerts the most significant influence on consumer switching, followed by flavor importance, while brand perception plays a comparatively smaller role. The mediation analysis further reveals that price acts as an intermediary between brand perception and switching behavior, as well as between flavor importance and switching behavior, reinforcing the central role of pricing strategies in the industry.The results suggest that Gudang Garam must reconsider its pricing model and explore cost-effective strategies to compete in the price-sensitive segments. Additionally, product diversification, particularly in flavored cigarette offerings, is critical in responding to shifting consumer preferences. Enhancing brand perception through modernized marketing strategies may also contribute to improving customer retention. These findings offer valuable insights for industry stakeholders, highlighting the importance of aligning pricing, product innovation, and brand positioning with evolving market demands.